Community environmental assessment for migrant seniors’ mental health: a multi-attribute decision-making model - Wu, Zeyu; Qi, Xiaopan; Qin, Jialin; Cai, Beini; Kuang, Shuo (Frontiers in Medicine, 2026)
IntroductionElderly migrants face significant mental health risks and social isolation within the context of global aging and mobility. As their daily activities are highly community-centric, the residential environment is a critical determinant of their well-being; however, a systematic assessment framework tailored to this population is lacking. This study aims to address this gap by identifying key community environmental factors influencing their mental health and employing the DANP-V model to construct a systemic methodology that elucidates complex inter-factor causalities and establishes prioritized improvement strategies.MethodsWe established a framework of community environmental factors based on the daily behaviors of elderly migrants. The Fuzzy Delphi Method (FDM) was used to screen and finalize 16 key indicators across six dimensions. The DANP-V model, a hybrid multi-criteria decision-making (MCDM) technique integrating DEMATEL, ANP, and VIKOR methods, was then applied to analyze the interrelationships and weights of these factors. The model was empirically tested through a case study in Qianshan Community, Zhuhai, China, using survey data from both domain experts (n=10) and elderly migrants (n=140).ResultsThe DANP-V analysis revealed a total performance gap of 0.495 for the case community, indicating substantial room for improvement. “Environmental Exposure” (D6, gap = 0.629) and “Self-Actualization” (D4, gap = 0.617) were the most deficient dimensions. Key criteria with the largest gaps included “Pet-Friendly Facilities” (C54, gap = 0.779), “Ambient Temperature” (C63, gap = 0.726), and “Ancestral Worship Sites” (C51, gap = 0.713). The Influential Network Relation Map (INRM) illustrated that factors like “Transportation & Mobility” (C53) and “Living Convenience Facilities” (C52) were influential predecessors, affecting other criteria.DiscussionThe DANP-V model provides a systemic approach to assess and improve community environments for elderly migrants’ mental health, moving beyond isolated factors to address root causes within an interconnected system. The case study demonstrates that critical gaps often lie in culturally-specific (e.g., ancestral worship) and emotion-supporting (e.g., pet-friendly) elements, which are frequently overlooked. The study offers a robust framework for policymakers and designers to develop targeted, effective community improvement strategies.